Hamstrings, quadriceps, and gluteal muscle activation during resistance training exercises - Garceau, L.; Lutsch, B.; Gary, A.; Szalkowski, C.; Wurm, B.; Ebben, W. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
This study evaluated hamstrings, quadriceps, and gluteal muscles activation during the back squat, deadlift, step-up, and lunge. Root mean square electromyographical data were analyzed for the eccentric and concentric phases during each exercise. Subjects included 16 women who performed 2 repetitions of each of the exercises at a 6 repetition maximum load. A repeated measures ANOVA revealed significant main effects (P=0.05) representing differences in muscle activation between the resistance training exercises all muscle groups (P=0.05) except for the rectus femoris, during the concentric phase (P=0.22). Based on these results, resistance training exercises can be prescribed based on how they best train the desired musculature.